The principle of recoil sealing from the perspective of Niklas Luhmann's systems theory - Bittar, Guilherme de Moraes (Atâtôt - Interdisciplinary Journal of Human Rights (UEG), 2021)
This article aims to establish an overview of the concepts and ideas of Niklas Luhmann's thought, to then carry out an analysis of the legal institute of the principle of the non-retrogression principle from the perspective of Luhmann's systems theory, and, consequently, assess the limits of and problems related to the factual ballast and the application of this institute to the needs and demands of the economic, political and moral systems. For the purpose, the basic lines of Luhmannian thought will be drawn, focusing on concepts such as autopoiesis, system, environment, functional differentiation, binary code, operative closure, structural couplings, irritation, systemic corruption, etc., and a a brief analysis of the non-retrogression principle and its treatment by the Brazilian legal doctrine, in order to observe it from the perspective of Luhmannian thought.